2014
DOI: 10.1177/2047487314536873
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease, cardiovascular disease and mortality: A prospective cohort study in a multi-ethnic Asian population

Abstract: In multi-ethnic Asian adults, lower eGFR and higher albuminuria were independently associated with incident CVD and all-cause mortality. These findings extend previously reported similar associations in Western populations to Asians and emphasize the need for early detection of CKD and intervention to prevent adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 36 publications
5
54
1
Order By: Relevance
“…The eGFR range in this study group was 25 to 188 mL/min/1.73 m2 with only 5.9% patients having an eGFR <45. The association of eGFR <45 with increased cardiovascular risk has been observed previously, but the minority of patients in this study lying in this range might explain why eGFR or other renal function markers did not interact with uACR as a predictor of events in this dataset. Albuminuria may be an earlier renal sign of increased cardiovascular event risk than eGFR, because it was observed in this population with mostly preserved kidney function.…”
Section: Discussionsupporting
confidence: 65%
“…The eGFR range in this study group was 25 to 188 mL/min/1.73 m2 with only 5.9% patients having an eGFR <45. The association of eGFR <45 with increased cardiovascular risk has been observed previously, but the minority of patients in this study lying in this range might explain why eGFR or other renal function markers did not interact with uACR as a predictor of events in this dataset. Albuminuria may be an earlier renal sign of increased cardiovascular event risk than eGFR, because it was observed in this population with mostly preserved kidney function.…”
Section: Discussionsupporting
confidence: 65%
“…The OR s of CVD and all-cause mortality were 1.54 and 2.21, respectively, in patients with eGFRs of <45 versus ≥60 ml·min −1 ·1.73 m −2 , and 2.81 and 2.34, respectively, in patients with UACRs of ≥300 versus <30 mg/g·Cr. [21] In an earlier study in the general population, a 2-fold increase in urine albumin concentration was found to be associated with a 1.29-fold increase in the risk for cardiovascular mortality. [22] It was reported that cardiovascular mortality was found to be two to three times higher in patients with Stage 3 or higher CKD than in individuals without renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously used the database for other studies. 21,22 MI was defined as either (1) definitive or clinical MI; or (2) death cases signed up by pathologists or physicians as MI, with or without necropsy done. Incident MI was identified by linkage with a subset of the National Registry of Diseases Office database: the Singapore Myocardial Infarction Registry, which captures all MI diagnosed and coded with International Classification of Diseases 9th Revision (ICD-9) 410 in all hospitals.…”
Section: This Ismentioning
confidence: 99%
“…We used the 2011 Singapore Population as the standard population for comparison. 22 Specifically, we used the Singapore Male population (consisting of 48.8% of the total Singapore population) for standardizing the male participants, and the Singapore Female population (consisting of 52.2% of the total Singapore population) for standardizing the female participants. 26 Age strata-specific (5-year age group) IR were calculated by weighing the proportions of the corresponding age strata in the population census.…”
Section: This Ismentioning
confidence: 99%